Studi Fenomenologi: Pengalaman Spiritualitas Klien Perempuan Dengan Chronic Kidney Desease (CKD) Yang Menjalani Hemodialisys Di RSUD Dr. H. Koesnadi Bondowoso. - Nugroho, Setiyo Adi; Rohman, Handono Fatkhur; hasanah, Mamlu’ul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Aspect of spirituality is one of the important issues in the care of female clients who undergo hemodialisys. The purpose of this study to explore more deeply about the meaning of the spirituality of female clients who undergo hemodialisys. This research plan uses qualitative with descriptive phenomenology approach. The study derives five themes: (1) relationship with God, (2) relationships with oneself, (3) relationships with others, (4) originators and inhibitors, and (5) client expectations. A total of 6 female participants by using purposive sampling. Data were collected by in-depth interviews and observations. Data analysis using selective and highlighting approach (the selective or highlighting approach). The results of this study participants changed in terms of worship is an increase in terms of worship. To that end, nurses can provide appropriate nursing interventions to help clients. Keywords : Chronic Kidney Disease, Hemodialysis, Spirituality, and Women.